Autonomous navigation system - Chew, Zhen Yi (Nanyang Technological University, 2024)
Autonomous robots and mobile vehicles have gained popularity and traction over the last decade in various industries such as security, manufacturing and transportation. By integrating autonomous capabilities into mobile robots, tasks can be performed without the need for human intervention, which improves operational efficiency, consistency and precision. These robots often need to navigate through complex environments while performing their tasks, requiring them to understand their surroundings in real-time. This paper aims to explore the integration of an autonomous navigation system with Unmanned Aeriel Vehicles (UAVs), focusing on the implementation of Simultaneous Localization and Mapping (SLAM) and path planning techniques. These methodologies enable UAVs to estimate their pose and orientation, allowing them to navigate safely and autonomously within their environments.